Fikih dalam Tafsir Berbahasa Sunda - Siti Novi Nafisah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
This article discusses the interpretation of fiqh verses in Sundanese Interpretation Raudhatul Irfan Fi Ma'rifat Al-Qur'an by KH. Ahmad Sanusi. By studying the law of fiqh we can know which rules to follow and know the limits. The law of fiqh can also be the basis of behaving and referral in making decisions. Interpretation of the Qur'an by local scholars who developed in Indonesia many who use the language of the region, one of which is Sundanese. Therefore, it would be interesting if this study discussed of the fiqh pattern in Sundanese interpretation. This research is a type of library research. Through a descriptive method approach, the author describes how the interpretation of some fiqh verses written in Sundanese in Tafsir Raudhatul Irfan Fi Ma'rifat Al-Qur'an. The primary source of this research is Tafsir Raudhatul Irfan Fi Ma'rifat Al-Qur'an by KH. Ahmad Sanusi written in Sundanese pegon scripts. The aim that the writer wants to achieve in this study is to find out how the characteristics of the fiqh pattern in Tafsir Raudhatul Irfan Fi Ma'rifat Al-Qur'an by KH. Ahmad Sanusi.